A (re)construção do perfil profissional do administrador contemporâneo - Bezerra, Sefisa (2020)
The present study intends to test the application of renewed learning practices through the use of interdisciplinary methods that can contemplate behavioral, emotional and specific aspects (intrapersonal and interpersonal intelligences) in the process of professional development among undergraduate students in Administration (n=478) from the University of the Acaraú Valley (Brazil). Based on the assumption that the introduction of renewed learning practices enables the introduction/reinforcement of knowledge, skills, abilities and attitudes that, in line with the expectations of the organizations and the aspirations of society, can translate into a more humanized contemporary management, a research paradigm has been defined that assumes two paths that integrate mixed methods in the collection and analysis of data: (1) a quantitative nature in order to assess the impact of the use of active learning practices; (2) a qualitative nature in order to understand the opinions of the course format, its development, use and learning. As such, the data were collected through the application of the Multiple Intelligences Inventory for Adults (MIIA), an instrument created by Armstrong and adapted from the Howard Gardner Multiple Intelligence Test. Regarding the treatment and analysis of the collected data, statistical procedures of a descriptive and inferential nature were favored through the statistical software SPSS. The results obtained reinforce the need to (re) think systematization and didactic procedures that are able to dynamize the learning in the context of the classroom and the development of the different dimensions / competences necessary and fundamental to the construction of the identity / profile of the professional of the administration / contemporary management.